Empowering Women Through Social Entrepreneurship Cooperatives for Women - Suharnanik, Suharnanik; Putri, Rizca Yunike (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
Women's cooperatives are one way to strengthen a person's capacity and possibilities for economic empowerment and involvement in more inclusive financial development. as a venue for enhancing the position of women both nationally and in the family economy. The purpose of this study is to get insight into the role that women's cooperatives play in social entrepreneurship initiatives for women. This paper examines the socio-cultural behavior of women engaged in the social entrepreneur field where they become part of the membership of a women's cooperative. The findings from the research study in this paper are that women have a culture that is more consistent, honest, and transparent in managing their social entrepreneurship, but is weak in terms of sustainability. Practical implications, this paper can provide input for policymakers regarding the development of women's potential in the field of social entrepreneurship. This research is still very rare because not all women are capable of engaging in social entrepreneurship. The value obtained in this research is the empowerment of women in the field of social entrepreneurship. This program prioritizes women's ability to identify problems as a source of socio-economic empowerment.